Patient-reported adverse events after colonoscopy in Norway - Hoff, Geir; de Lange, Thomas; Bretthauer, Michael; Buset, Magne; Dahler, Stein; Halvorsen, Fred-Arne; Halwe, Jörg Michael; Heibert, Mathis; Høie, Ole; Kjellevold, Øystein; Moritz, Volker; Sandvei, Per; Seip, Birgitte; Aabakken, Lars; Holme, Øyvind (Endoscopy, 2017)
Background and aims Patient-reported outcome measures are increasingly important in healthcare. European guidelines have recommended inclusion of patient feedback to capture adverse events due to colonoscopy, but this is rarely implemented. Methods The Norwegian Quality Assurance network for endoscopy (Gastronet) collects patient-reported outcome for colonoscopies. Free-text comments on patient reports from January to December 2015 were characterized as positive or negative. All negative free-text comments were scrutinized for information that might suggest colonoscopy-related adverse events. We identified severe adverse events with and without admission to hospital. Results We included 16 552 outpatient colonoscopies performed at 21 hospitals. A total of 11 248 procedures (68 %) were accompanied by a patient feedback report, of which 2628 (23 %) had free-text comments (2196 [20 %] characterized as positive and 432 [3.8 %] as negative). These negative free texts on patient reports revealed 15 post-colonoscopy hospital admissions due to adverse events that had not been registered in the colonoscopy report. This increased the number of hospital admissions caused by adverse events from 3 (0.03 %) to 18 (0.16 %). In addition, there were 14 patient reports of severe events without hospital admission. Therefore, a total of 29 severe adverse events reported by patients were missed by conventional documentation in the colonoscopy form.Conclusion It is feasible to implement patient feedback as routine reporting to capture the full picture of colonoscopy-related adverse events. Some patients experience significant complications that are not recorded through any registries. Patient feedback forms should be tailored to capture adverse events after colonoscopy that are otherwise not easily disclosed.